Platinum share prices and the Marikana tragedy: an event study - Sunga, Tapuwa Terence (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2014)
An event study is an economic tool of analysis that has begun to gain popularity in recent empirical literature. It is a technique that gives a researcher the opportunity to map out the reaction of a firm's stock to an event, usually making use of daily or monthly data. However, up to this point, event study methodology has generally been applied to more traditional phenomena capable of affecting equity value, such as dividend and macroeconomic policy announcements, and there have only been a few exceptions to this. This study looks at what impact the tragic shootings at Lonmin mine in Marikana on August 16th 2012 had on the share prices of platinum mining firms based in South Africa using event study methodology. It makes use of the technique to investigate how the share prices responded to the tragedy over a number of trading days, including the day of the shootings. To be best of our knowledge, no attempt has been made to analyse the impact on share prices using events of this nature. For the investigation, daily returns data was used for each firm. The abnormal returns and cumulative abnormal returns to each were then calculated and compared with their respective expected returns in order to determine whether investors in the shares of that particular firm reacted positively, negatively or not at all. The evidence found suggests that tragedies of this nature are capable of influencing share prices in the same manner as more traditional economic phenomena. Overall, only one firm was found to have been negatively affected by the shootings in a persistent manner, while the shares of the other firms examined reacted in a manner that was positive overall, but varied according to individual firm characteristics such as size. These finding conformed to our a priori expectations. In addition, the results also confirm the benefits of applying event study methodology to a wide variety of phenomena that fall outside the boundaries usually associated with business.
Keywords: Marikana (Rustenburg, -- South Africa); Massacres -- South Africa -- Rustenburg; Stocks -- Prices -- South Africa; Stocks -- Prices -- Mathematical models